Artista/Câmara de maravilhas - Brengel, Ana Maria Vieira [UNESP] (2014)
The present dissertation has two different purposes: to register the artist’s production – including sculptures, objects, installations, paintings, performances, artistic experiences – and to present a theoretical text. For both cases, the research focuses on the exhibition space and how art works are exhibited, comparing the present spaces for exhibition and the Cabinets of Curiosities – private collections presented to a selected public, mostly during the 17th and 18th centuries, which can be regarded as the predecessors of modern museums